Capacity and kinetics of zearalenone adsorption by Geotrichum candidum LG-8 and its dried fragments in solution - Jiao, Fengping; Cui, Xianping; Shi, Shujin; Jiang, Guozheng; Dong, Mingsheng; Meng, Ling (Frontiers in Nutrition, 2024)
The application of LG-8 and its dry fragments as zearalenone (ZEN) adsorbents was investigated. The study showed that Geotrichum candidum LG-8 and its fragments dried at 55°C or through lyophilization are able to adsorb around 80% of ZEN. However, besides in water and 55°C-drying conditions, SEM indicated that higher 90% of ZEN binding tended to occur when cell walls of fragments were intact with less adhesion among themselves. Notably, ZEN/LG-8 fragments complexes were quite stable, as only 1.262% and 1.969% of ZEN were released after successive pH treatments for 4 h and 5 min. The kinetic data signified that adsorption of ZEN onto LG-8 fragments followed well the pseudo-first-order kinetic model. Isotherm calculations showed Langmuir model was favourable and monolayer adsorption of ZEN occurred at functional binding sites on fragments surface. Therefore, we conclude that it can be an alternative biosorbent to treat water contained with ZEN, since LG-8 is low-cost biomass and its fragments have a considerable high biosorption capacity avoiding impacting final product quality and immunodeficient patients.